Improving Children's Fine Motor and Cognitive Skills Through Watercolor Finger Painting Activities - Tabun, Norlianti L; Maarang, Matrheda; Lily, Netry Maria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article examines the support offered in learning finger painting for the Indria Mola-Kalabahi study group. The aim of this program is to assist young children in early development through finger painting to improve their cognitive abilities and fine motor skills. This task seeks to create a solid developmental base, promoting children's development and equipping them for a successful future. The execution of this program occurred in three phases: 1) Planning, 2) Implementation, and 3) Assessment. Students and instructors from the PG-PAUD Study Program at Universitas Tribuana Kalabahi took part in the project. The youngsters participating ranged from 4 to 6 years old. The finger painting activity demonstrated success in enhancing cognitive and fine motor skills by utilizing readily available and inexpensive materials. The outcomes of the children's finger paintings showed evident advancement during the activity.